Tingkat Kepuasan Mahasiswa Terhadap Pelayanan Dosen Pendidikan Agama Islam Menggunakan Fuzzy C-Means (Studi Kasus Di Universitas Kaltara) - Abdul Arif; Dady Sulaiman; Ratna Dwi Christyanti (Jurnal Ilmiah Teknologi Informasi Asia, 2022)
Kaltara University (Unikaltar) is a private university located in North Kalimantan. Unikaltar conducts development efforts on stabilizing the quality of management and human resources. Based on this, it is necessary to measure the level of student satisfaction with the service of lecturers in teaching, especially Islamic education. The purpose this study to measure the level of student satisfaction with the ministry of lecturers in teaching Islamic education. The method used is fuzzy C-Means algorithm with GUI MATLAB. The stages of the research method that will be carried out include data collection, data input, Validity and Reliability Test, data classification using Fuzzy C-Means algorithm with GUI MATLAB, and analyzing output into two groups, namely group C1 (Dissatisfied) and group C2 (Satisfied). Satisfaction levels in odd semesters are high where the number of C1 (27%) and C2 (73%) groups is also high, with the number of C1 (30%) and C2 (30%) groups.